Chemosynthesis influences food web and community structure in high-Arctic benthos - Åström, Emmelie K. L.; Carroll, Michael L.; Sen, Arunima; Niemann, Helge; Ambrose Jr., William G.; Lehmann, Moritz F.; Carroll, JoLynn (Marine Ecology Progress Series, 2019)
Cold seeps are locations where seafloor communities are influenced by the seepage of methane and other reduced compounds from the seabed. We examined macro-infaunal benthos through community analysis and trophic structure using stable isotope analysis at 3 seep locations in the Barents Sea. These seeps were characterized by high densities of the chemosymbiotic polychaetes Siboglinidae, clade Frenulata (up to 32120 ind. m-2), and thyasirid bivalves, Mendicula cf. pygmaea (up to 4770 ind. m-2). We detected low δ13C signatures in chemosymbiotic polychaetes and in 3 species of omnivorous/predatory polychaetes. These δ13C signatures indicate the input of chemosynthesis-based carbon (CBC) into the food web. Applying a 2-source mixing model, we demonstrated that 28-41% of the nutrition of non-chemosymbiotic polychaetes originates from CBC. We also documented large community variations and small-scale variability within and among the investigated seeps, showing that the impact of seepage on faunal community structure transcends geographic boundaries within the Barents Sea. Moreover, aggregations of heterotrophic macro- and megafauna associated with characteristic seep features (microbial mats, carbonate outcrops, and chemosymbiotic worm-tufts) add 3-dimensional structure and habitat complexity to the seafloor. Cold seeps contribute to the hydrocarbon-derived chemoautotrophy component of these ecosystems and to habitat complexity. These characteristics make the cold seeps of potential high ecological relevance in the functioning of the larger Arctic-Barents Sea ecosystem Chemosynthesis influences food web and community structure in high-Arctic benthos publishedVersion